Wayfinding: How Ecological Perspectives of Navigating Dynamic Environments Can Enrich Our Understanding of the Learner and the Learning Process in Sport - Woods, Carl T. (Sports Med Open, 2020)
Wayfinding is the process of embarking upon a purposeful, intentional, and self-regulated journey that takes an individual from an intended region in one landscape to another. This process is facilitated through an individual’s capacity to utilise temporally structured, functional actions embedded within a particular environmental niche. Thus, individuals learn of their performance landscapes by experiencing them through interactions, detecting and exploiting its many features to ‘find their way’. In this opinion piece, we argue that these ecological and anthropological conceptualisations of human navigation can, metaphorically, deepen our understanding of the learner and the learning process in sport, viewed through the lens of ecological dynamics. Specifically, we consider sports practitioners as (learning) landscape designers, and learners as wayfinders; individuals who learn to skilfully self-regulate through uncharted fields (composed of emergent problems) within performance landscapes through a deeply embodied and embedded perception-action coupling. We contend that, through this re-configuration of the learner and the learning process in sport, practitioners may better enact learning designs that afford learners exploratory freedoms, learning to perceive and utilise available opportunities for action to skilfully navigate through emergent performance-related problems. We conclude the paper by offering two practical examples in which practitioners have designed practice landscapes that situate learners as wayfinders and the learning process in sport as wayfinding.